2023
DOI: 10.2147/copd.s391487
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Regulation of Wnt Pathway-Related Progression of Chronic Obstructive Pulmonary Disease Airway Lesions

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic disease associated with inflammation and structural changes in the airways and lungs, resulting from a combination of genetic and environmental factors. This interaction highlights significant genes in early life, particularly those involved in lung development, such as the Wnt signaling pathway. The Wnt signaling pathway plays an important role in cell homeostasis, and its abnormal activation can lead to the occurrence of related diseases such as asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…[ 39 ] On the one hand, pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL-1β, IL-11, and IL-17, govern bone resorption by promoting osteoclast activity. [ 40 ] On the other hand, these cytokines directly impede bone formation. The Wnt/β-catenin signaling pathway plays a pivotal role in skeletal development, significantly influencing the differentiation of mesenchymal stem cells into mature osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 39 ] On the one hand, pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL-1β, IL-11, and IL-17, govern bone resorption by promoting osteoclast activity. [ 40 ] On the other hand, these cytokines directly impede bone formation. The Wnt/β-catenin signaling pathway plays a pivotal role in skeletal development, significantly influencing the differentiation of mesenchymal stem cells into mature osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, acting as a key inducer of DKK-1 (a Wnt antagonist), can suppress osteoblast differentiation. [ 40 , 41 ] According to findings from the Xinxiang Rural Cohort Study conducted in China, a decrease in BMD of 0.1 g/cm 2 was associated with a reduction of 53.0 mL in forced vital capacity (FVC) and 33.5 mL in forced expiratory volume in 1 second (FEV1) after adjusting for possible confounding variables using linear regression analysis, which suggests that a decline in BMD is linked to impaired lung function. [ 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…The highly conserved Wnt gene, discovered in 1982, encodes a lipid-modified glycoprotein known as the Wnt protein, which consists of 350–400 amino acids ( Ng et al, 2019 ). To date, 19 Wnt proteins have been identified as ligands that bind to the Frizzled (FZD) receptor, low-density lipoprotein receptor-related protein (LRP) receptor, and other receptors on the cell surface to activate signaling pathways with various functions during embryonic and adult development ( Liu, Huo & Cheng, 2023 ) ( Fig. 1 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Moreover, WISP1 has been found to be increased in alveolar epithelium type II cells in patients with idiopathic pulmonary fibrosis (IPF) and correlates with (myo)fibroblast activation, ECM deposition, and epithelial-mesenchymal transition ( 13 15 ). Furthermore, it has been reported that β-catenin signaling contributes to ECM production by lung fibroblasts and their differentiation to myofibroblasts in chronic obstructive pulmonary disease (COPD) ( 24 , 25 ). On the other hand, suppressed Wnt/β-catenin signaling has been suggested to play an essential role in airway inflammation in COPD by promoting the production of inflammatory cytokines via a peroxisome proliferator-activated receptor-δ/p38 signaling pathway in airway epithelial cells ( 26 ).…”
Section: Introductionmentioning
confidence: 99%